The Impact of Covid-19 on the Economy in Kupang City (Case Study of Penfui Village) - Delviana Meak; Fransina W. Ballo; Maria Indriyani Hewe Tiwu (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to clarify the social and economic impact of the COVID-19 pandemic on the lives of the people of Penhui village. This study uses a mixed method of quantitative and qualitative research. Data collection techniques include observation, interviews, and documentation. The data analysis techniques used in this study are data reduction, data presentation, and validation or drawing of conclusions. The findings show that the impact of the COVID-19 pandemic is affecting the economic survival of households, causing household decline and instability. Personal consumption, the most important pillar of the economy, is sluggish, which is ultimately affecting the economic situation of small and medium-sized businesses